The Effect Of Hydrogen Diffusion In Orthodontic NiTi Archwire - Azaman, Amirul Fahmi (Universiti Sains Malaysia, 2022)
The application Nickel-Titanium alloy has been widely used in orthodontics because of its superior mechanical qualities, biocompatibility, ductility, corrosion resistance, reduced elastic modulus, and specific features such as superelasticity and form memory effect [1]. When utilized in orthodontic treatments, nickel-titanium alloy is frequently exposed to the oral environment, which commonly causes fractures in the orthodontic wires. In this project, the deformation behavior as well as the thermo-mechanical properties of the NiTi superelastic wires has been investigated immediately after charged with hydrogen and aged at different time intervals. The specimen’s mechanical deformation behavior will be tested using the Universal Testing Machine (UTM) while the thermo-mechanical behavior will be investigated using the Differential Scanning Calorimetry (DSC). Experimental results show that compressibility and recovery of orthodontic NiTi wires were dependent on the period which the wires were charged and aged. From DSC analysis, the NiTi wires shows different behaviors with different charging and ageing time. During both the reverse transformation and forward transformation, the height of the peak and number of peaks for samples with different charging time and ageing time are different in comparison with the as-received sample. When charged for 24 hours and aged for 14 days, two peaks were obtained during the martensite to austenite phase transformation which differs from the all the other specimen which indicated two R-phase for that particular phase transformation. Moreover, the deformation behavior obtained from the tests show that specimens that were charged with hydrogen and aged at room temperature produced higher number of deflection for the same value of bending force compared to the as-received specimen. It is speculated that longer hydrogen charging and aging period will allow more hydrogen to diffuse into the wire. This hydrogen diffusion affected the microstructure of the NiTi archwire and caused the reduction in the elasticity of the wire.